Kepemimpinan Transformasional Strategi Mengatasi Tantangan dan Memanfaatkan Peluang dalam Kepemimpinan Transformasional - Dwi Ida Puspita sari, Dwi Ida; Aidillah, Muhammad Rafli; Gunawan, Muhammad Henry (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2024)
This article aims to describe the concept of transformative leadership in organizations or companies. This article uses a qualitative descriptive approach with a library research method. The results of this article generally explain transformational leadership, including the definition, principles, styles, various factors, characteristics, steps, advantages, and disadvantages of transformational leadership. The conclusion obtained in this article is that leadership with a new approach is an inevitable need when facing the demands of fast-paced times. One of them is the need for a transformative leadership model that can develop the potential of oneself and subordinates innovatively, empower staff and organizations with changes in thinking, develop vision, understanding, and comprehension of organizational goals, and bring the organization towards sustainable change